2009
DOI: 10.2353/ajpath.2009.080318
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A within Sunlight Induces Mutations in the Epidermal Basal Layer of Engineered Human Skin

Abstract: The ultraviolet B (UVB) waveband within sunlight is an important carcinogen; however, UVA is also likely to be involved. By ascribing mutations to being either UVB or UVA induced, we have previously shown that human skin cancers contain similar numbers of UVBand UVA-induced mutations, and, importantly, the UVA mutations were at the base of the epidermis of the tumors. To determine whether these mutations occurred in response to UV, we exposed engineered human skin (EHS) to UVA, UVB, or a mixture that resembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 52 publications
(69 reference statements)
3
38
0
2
Order By: Relevance
“…The solar UV spectrum is made up of a combination of UVA (ϳ95%) and UVB (ϳ5%) wavelengths, both of which make significant contributions to skin cancer development by damaging DNA 70,71 and suppressing adaptive immune responses. 18,46,72 The presence of IL-33-producing cells deep within the dermis of UVB but not UVAexposed skin suggested that a UVB-induced soluble factor was responsible.…”
Section: Discussionmentioning
confidence: 99%
“…The solar UV spectrum is made up of a combination of UVA (ϳ95%) and UVB (ϳ5%) wavelengths, both of which make significant contributions to skin cancer development by damaging DNA 70,71 and suppressing adaptive immune responses. 18,46,72 The presence of IL-33-producing cells deep within the dermis of UVB but not UVAexposed skin suggested that a UVB-induced soluble factor was responsible.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well documented that DNA is the main critical cellular macromolecule for determining the carcinogenic effects of solar radiation (7)(8)(9). This received strong support from the delineation of mutagenic effects of UVB and UVA components (10)(11)(12)(13)(14) with the observation of UVB-induced C fi T transition and CC fi TT mutations at bipyrimidine sites in p53 genes of skin tumors (8,15). It has been also shown that C fi T transitions are generated in human skin by UV radiation within the 310-340 nm range at 5-methylcytosine containing bipyrimidine sites in CpG rich sequences (10,16).…”
Section: Introductionmentioning
confidence: 99%
“…Results of another study suggest that T-G transversion is a UVA "signature" (Drobetsky et al, 1995). UVA-specific lesions in the p53 gene have been detected in skin constructs and squamous tumours (Agar et al, 2004;Huang et al, 2009). In contrast, in vivo studies using "Big Blue" mice, and in vitro data, suggests that UVA-induced mutations are mainly of the pyrimidine dimer type (Mouret et al, 2006;Besaratinia & Pfeifer, 2008;Runger & Kappes, 2008).…”
Section: Evidence Of Uva Causality In Melanomamentioning
confidence: 99%